Situational copying strategies for the employees of the Federal service of the rosgvardi army - T. R. Gizatullin; D. A. Mukhametova; D. R. Tansykkuzhina; V. N. Tsygan; L. A. Kuzhina; L. V. Lyamina; L. R. Akhmadeeva (Сеченовский вестник, 2019)
The article discusses the ﬁrst results of studies of coping strategies of servicemen of the structure of Rosgvardia.The purpose of the study was to study the speciﬁcs and to analyze the coping strategies of the rank and ﬁle and the command structure of mobile special forces units (OMON) of the Federal service of troops Rosgvardia.Materials and methods. Underwent questionnaire survey 65 members of OMON of the Federal service troops Rosgvardia. The working activity of the presented group of people is associated with the frequent impact of stress factors. The questionnaire of coping with stress in adaptation of Rasskazova-Gordeeva-Aspen was used as a method. Results. After analyzing the data, we determined the frequency of choice of riot police coping strategies in diﬃcult or problematic situations for them. Conclusion. The data collected can be useful for the development of rehabilitation programmes for military personnel, as well as help to expand the database of existing data in the study of coping strategies.